Strength training - Reynolds, F.
. In the paragraphs that follow, you'll find three key power-building exercises that are easy to carry out, won't take much of your time, and will rejuvenate your running - because they replicate key motor movements involved in the process of running. 1) The high-bench step-up 2) One-leg squat 3) One-leg hops in place